(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study’s objective was to predict Kabaddi playing ability among college players based on a few anthropometrical and physical variables. One hundred forty-four male intercollegiate Kabaddi players between the ages of 18 and 25 were chosen at random from a number of colleges in the state of Hyderabad in India. The subjects were taken as subjects because they had played Kabaddi for at least three years and only represented their college teams